(untitled) (Indo-MathEdu Intellectuals Journal, 2024)
This research is motivated by the fact that the number of students who have low mathematical literacy skills is caused by various factors. One of the factors that affects mathematical literacy ability is learning motivation. This study aims to determine the ability of mathematical literacy when viewed from the learning motivation of students. This type of research is quantitative descriptive. The sample in this study is grade XI students of SMA Negeri 2 Padang Panjang. The sample selection technique in this study uses the Stratified random sampling technique where the sample is selected based on strata. The instrument used in this study is test questions in the form of essays to see students’ mathematical literacy skills. Data analysis was carried out descriptively on all research data. The results showed that the average mathematical literacy ability was 50 which was classified as low. If viewed from high learning motivation is classified as medium with an average score of 69, when viewed from medium learning motivation has low mathematical literacy skills with an average score of 56 and mathematical literacy ability reviewed from low learning motivation is classified as low in the low category with an average score of 25